Discourses on employment policy and labor rights in Peru - Cáceres Paredes, Joel (2020)
Starting from the identification of the importance of the discourses to understand social life and the analysis of employment policy, this article identifies the lines of discussion on the scope of labor rights or the policy of employment. Employment in the written press in Peru. In this way, based on an empirical study, it is revealed that these lines of discussion are not, strictly speaking, neutral, but rather obey certain ideas of economic and social policy that can guide the scope of labor legal norms, such as by example of flexibility-reduction of labor rights.